PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN AKHLAK SISWA KELAS V DI SDN BABAKANMADANG 02 BOGOR - Khaidir Fadil; Muhammad Jaelani; Kholil Nawawi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
Islamic religious education learning is not only taught about how a Muslim's obligation to worship, but in learning Islamic religious education is taught by educators how to have good morals. The purpose of this study was to determine the morals of fifth grade students at SDN Babakanmadang 02 Bogor, to determine the implementation of Islamic Religious Education learning on the formation of student morals at SDN Babakanmadang 02. This research uses a quantitative approach with survey techniques. The results of this study are the morals of fifth grade students at SDN Babakanmadang 02 Bogor in the good category with a mean (average) value of 68.97 or in the interval 68 - 84 which means that the morals of fifth grade students at SDN Babakanmadang 02 Bogor are in the good category. Learning of Islamic Religious Education in class V SDN Babakanmadang 02 Bogor is in the good category with a mean (average) value of 68.85 or in the interval 68 - 84 which means that the learning of Islamic religious education in class V SDN Babakanmadang 02 Bogor is in the good category. Based on the results of the significance test (f test), the results of the Fcount value 8.554> Ftable 4.08 with Sig. 0.000 < 0,005. If Fcount> Ftable sig value < a (0.05) then Ha is accepted and Ho is rejected. Therefore, the results are significant, and the hypothesis proposed by the researcher is accepted. Thus, there is a significant influence between Islamic Religious Education Learning on Student Morals.